Augmented Reality Based Mobile Learning System Design in Preschool Education - Baykara, Muhammet; Gurturk, Ugur; Atasoy, Bedirhan; Percin, Brahim (Ieee, 2017)
With the development of computers, the Internet and mobile technologies, different needs have emerged for people and different solutions have been discovered to meet these needs. One of the critical areas which are considered as the main factor in creating the tomorrow of human beings where a careful study should be done is the education and teaching. Many technologies are being used and various methods are being tried to develop and make the field of education and training more productive. Among these methods, the use of Augmented Reality (AR) technology is emerging in a wide range and scope with advancing technology and it is becoming widespread. In AR technology, the message and information to be given are visualized by visual and auditory methods (3D). In this study, a mobile-based augmented reality application was implemented for pre-school education. In the study, animals and plants were visualized in both English and Turkish as 3D, and at the same time, animals were presented with 3D visualization. In addition to providing audiovisual and visual material in pre-school education, the study will assist in children' development and accelerate the learning process.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: augmented reality; education; mobile devices; virtualization; mobile learning